'The enemy within': Campaign attention and motivated reasoning in voter perceptions of intra-party conflict. (September 2021) - Plescia, Carolina; Kritzinger, Sylvia; Eberl, Jakob-Moritz
In spite of broad interest in internal party dynamics, with previous literature relatedly demonstrating that voters are not oblivious to party infighting, very little attention has been paid to the antecedents of voter perceptions of intra-party conflict. This article addresses this research deficit with the support of empirical evidence gathered over the course of the 2017 Austrian national election campaign. The study examines variations in perceived intra-party conflict over time, both across parties and within the same party. We find that although voter perceptions largely mirror actual distinctions in intra-party fighting, conspicuous individual-level variations can also be identified owing to attention to the election campaign and motivated reasoning in information processing. These results have important consequences for our understanding of voter perceptions of intra-party conflict and the role of election campaigns, with potential implications for party strategies during election campaigns.